Comparison of morphine with and without fentanyl for epidural analgesia after major abdominal surgery - Chrubasik, Sigrun; Chrubasik, Joachim; Pfisterer, Markus; Hage, Rolf; Schulte-Mönting, Jürgen (Regional anesthesia, 1996)
Background and Objectives The study compared bolus injection of fentanyl versus morphine to supplement epidural infusion of morphine for pain relief after major abdominal surgery. - Methods Postoperative epidural analgesia was activated by patient request for pain relief. Thirty patients were given a loading dose (random assignment, double-blind administration) of 2 mg of morphine (group M, n = 15) or 60 μg of fentanyl (group F/M, n = 15), along with an epidural infusion of 0.2 mg/h of morphine. Additional boluses of 0.5 mg of morphine (group M) or 25 μg of fentanyl (group F/M) were given according to individual need. If patients were painfree for 3 hours, the infusion rate for morphine was reduced by 50%. - Results Both treatments provided similar degrees of analgesia, although onset time was shorter for the F/M group (P < .05). To obtain 24 hours of analgesia, group M needed 18.0 mg of morphine, while group F/M needed 4.7 mg of morphine and 1.48 mg of fentanyl. For group M, mean serum concentrations of morphine decreased from 18 ng/mL at 1 hour from the start of treatment to 5 ng/mL at 24 hours. For group F/M, serum morphine stayed at approximately 4 ng/mL, but serum fentanyl increased from 0.28 ng/mL at 5 minutes to about 0.8 ng/mL at 16 hours. - Conclusions When fentanyl is added continuously to epidural morphine, the resulting higher total serum levels of opioids during prolonged treatment may increase the risk of respiratory depression. Combining the two opioids for the loading dose, however, may be valuable to shorten the onset time of analgesia.